Radiation and revolution - Kōso, Iwasaburō, 1955- (Thought in the act., 2020)
"In RADIATION AND REVOLUTION, political critic and activist Sabu Kohso positions the 2011 Fukushima nuclear disaster as an impetus for a renewed planetary politics. For Kohso, the "Event" offers an insight into the tension of, one the one hand, the World, as defined by capitalist nation-states, and on the other hand, the Earth, which is driven by interconnected planetary flows and entanglements. Focusing particularly on the effect of the Fukushima disaster on revolutionary politics, Kohso outlines three conceptual and eschatological ways to think about the Event: Disaster, Catastrophe, and Apocalypse. In this schema, Disaster signifies the real experience of people in the world: the immediate devastation brought on by nuclear disaster and the consequential tsunami, and the ongoing havoc radionuclides wreak on the planet. Catastrophe points to the failure of political and social institutions, and the rearrangement of power in the wake of nuclear disaster. Lastly, Apocalypse speaks to the affective and agential aspects of the disaster, and how people experience the aftermath of Fukushima. While Kohso readily admits that eschatological views can be harnessed by capitalist nation-states as a means to reproduce under the guise of patriotism and redevelopment, he also crucially argues that eschatology has been used historically by revolutionary people as a means to think about a rebirth of the world. In the latter reading, which Kohso suggests we follow, eschatological views of disaster provide a space for people to imagine other types of planetary cohabitation that is not limited to capitalist nation-states. The book comprises four chapters and an epilogue. Chapter 1 focuses on the Disaster of the Event, and offers an account of the nuclear disaster drawn from the author's own observations, stories from friends, and published reports in Japan. Chapter 2 illuminates the context for the event, providing a geo-history of the Japanese nation-state as an insular territory constituted in response to catastrophes, both natural (atmospheric and tectonic) and man-made (Western colonialism). In this chapter, Kohso frames Japan as a prosperous society bookended by two nuclear disasters: Hiroshima/Nagasaki and Fukushima. Chapter 3 tackles the mechanism whereby nuclear production continues to proliferate despite the calamities it has caused. Here the sense of Apocalypse is the predetermined future of a radioactive planet, rather than the immediate end of the world-a course charted by 'nuclearized capitalism' or capitalism that ensures its endless reproduction by assimilating itself to the nuclear industry. Chapter 4 compares the revolutionary struggles of 1968 to those of the post-Fukushima world. In the epilogue, Kohso poses questions about the "End": What does the end of Japan look like? What does the end of the human world mean?"--